Comparison of the head and neck position of elite dressage horses during top-level competitions in 1992 versus 2008 - Lashley, M. J. J. O.; Nauwelaerts, S.; Vernooij, J. C. M.; Back, W.; Clayton, H. M. (The Veterinary Journal, 2014)
Among veterinary surgeons, interest has recently increased in the role of the horse's neck as a causative factor in complex locomotor disturbances. Specifically, controversy surrounds the trend for the head to be carried behind the vertical (BHV) in contravention of Fédération Equestre Internationale (FEI) rules. The aim of this study was to determine whether the head angulation of elite dressage horses has changed over the last 25 years, and whether head angulation correlates with the competition score awarded. Head angle was measured from videos recorded during the Grand Prix test at the 1992 Olympic Games and the 2008 World Cup Final, during collected canter (CC), collected trot (CT), passage (Pa), and piaffe (Pi). Head angulations were BHV in CC and CT in both 1992 and 2008. The likelihood of being BHV during Pa or Pi was significantly greater in 2008 than in 1992 (P < 0.05). Higher scores correlated significantly with head positions that were further BHV during Pi in 2008 (P < 0.05). Head angulations were orientated BHV in all paces in 2008, whereas in 1992 this was only the case for CT and CC. These findings support the hypothesis that, in recent years, FEI dressage judges have not penalised horses for a head position BHV. The findings also support the need for further studies of the effects of head and neck position on the health of horses.